Exploring the role of therapeutic drug monitoring and regular supervision in optimizing quality of life in patients of bipolar affective disorder receiving lithium therapy in a tertiary care teaching hospital: a prospective observational study - Munshi, Santanu; Pal, Agnik (International Journal of Research in Medical Sciences, 2020)
Background: Lithium is considered first line drug effective in treating manic and mixed episodes of bipolar affective disorders throughout the globe. But the chronic and heterogenous nature of disease, along with toxicity of lithium often make patients non-adherent to medication as well as diminished health related quality of life. Present study was done to find out the prospect of regular supervision and follow up with therapeutic drug monitoring in optimization of lithium therapy based on health-related quality of life outcomes. Methods: It was a prospective, non-randomized, observational study of a cohort of subjects who are suffering from bipolar affective disorders and on lithium therapy. Patients were regularly followed up with therapeutic drug monitoring and personalized interview with questionnaires like WHO Quality of Life Score (QOL-Bref), Montgomery-Asberg Depression Scale (MADRS) and Medication Adherence Rating Scale (MARS). Results: Results revealed there was significant improvement in health-related quality of life of patients who were monitored with therapeutic drug monitoring and prescribed lithium therapy. Conclusions: Hence to maintain patients’ quality of life improved throughout the cycle of bipolar disorder spectrum, regular follow-up visits with monitoring of serum levels of lithium is needed, so that adverse effects would be minimal and adherence to medication become optimal. These optimal dosing resulting in optimal benefit to patients can be achieved with the involvement of clinical pharmacological consultation.